Natural law theories in the early Enlightenment - Hochstrasser, T. J. (Tim J.) (Ideas in context ;, 2000)
"In this study T.J. Hochstrasser analyses and explains the development of natural law theories in Germany between Grotius and Kant. Particular attention is paid to Samuel Pufendorf and his followers, who incorporated many of the key theoretical insights of Thomas Hobbes into German political theory, and evolved a natural law theory based on human sociability and a self-sufficient concept of human reason. In so doing, they fostered a new methodology in German philosophy, eclecticism, which remained a major creative force in intellectual life down to the emergence of Kantian idealism.